The Influence of Home Environment and Habits on Pulmonary Tuberculosis Transmission in Teminabuan South Sorong District - Imelda Naolin; Ishaq Iskandar; Arlin Adam; Zamli (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The 2023 report from the Tuberculosis Working Group of the Directorate for Prevention and Control of Communicable Diseases, Ministry of Health of the Republic of Indonesia, showed an increase in detected pulmonary TB cases from 724,309 cases in 2022 to 821,200 cases in 2023. This increase aligns with the coverage rate of pulmonary TB rising from 68% in 2022 to 77% in 2023. The estimated detection of pulmonary TB cases in Indonesia from 2023-2024 is around 1,060,000 cases. At the provincial level, the case notification achievements showed that West Papua Province had a notification coverage of 112%, while West Papua Province had only 66%. Objective: The aim of this research is to examine the influence of physical environmental factors at home and the habits of pulmonary TB sufferers on the incidence of pulmonary TB as a factor in the transmission of pulmonary TB in South Sorong Regency. Method: The method used in this research is quantitative analysis with a cross sectional approach by carrying out logistic regression analysis. Result: The results of the study showed that the type of floor, humidity, the habit of opening and closing windows, cough etiquette and the habit of expelling phlegm were related to the incidence of pulmonary TB. There is no relationship between lighting levels, residential density, ventilation area, temperature and smoking habits on the incidence of pulmonary TB. The habit of expelling phlegm is the variable that has the most influence on the incidence of pulmonary TB (aPR 7.630 95%CI 1.991-29.242).. Conclusion: This research recommends promotion of stone ethics and monitoring of the housing conditions of pulmonary TB sufferers. Evaluation of programs and infrastructure improvements by the South Sorong District Health Service.